2022
DOI: 10.3390/healthcare10040647
|View full text |Cite
|
Sign up to set email alerts
|

Co-Produce, Co-Design, Co-Create, or Co-Construct—Who Does It and How Is It Done in Chronic Disease Prevention? A Scoping Review

Abstract: Co-production in health literature has increased in recent years. Despite mounting interest, numerous terms are used to describe co-production. There is confusion regarding its use in health promotion and little evidence and guidance for using co-produced chronic disease prevention interventions in the general population. We conducted a scoping review to examine the research literature using co-production to develop and evaluate chronic disease prevention programs. We searched four electronic databases for art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…McGill et al in their scoping review of 71 co-produced interventions for the prevention of chronic disease highlighted the interchangeable use of co-words such as 'co-design', 'co-create' and 'co-develop' when describing the involvement of end users or intermediaries. 69 In this review we chose to include studies that demonstrated a partnership with consumers (as aligned with the final two levels on the IAP2 Public Participation Spectrum 15 ) to provide consistency in our definition. When considering this approach alongside the three main arguments of public involvement in research as outlined in Greenhalgh et al, genuine co-design should acknowledge that consumers have the right to input into researching their condition, increase its relevance to consumers and dissemination beyond academic audiences and form alliances with consumers (knowledge co-constructed with researchers and the public) to increase accountability and transparency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McGill et al in their scoping review of 71 co-produced interventions for the prevention of chronic disease highlighted the interchangeable use of co-words such as 'co-design', 'co-create' and 'co-develop' when describing the involvement of end users or intermediaries. 69 In this review we chose to include studies that demonstrated a partnership with consumers (as aligned with the final two levels on the IAP2 Public Participation Spectrum 15 ) to provide consistency in our definition. When considering this approach alongside the three main arguments of public involvement in research as outlined in Greenhalgh et al, genuine co-design should acknowledge that consumers have the right to input into researching their condition, increase its relevance to consumers and dissemination beyond academic audiences and form alliances with consumers (knowledge co-constructed with researchers and the public) to increase accountability and transparency.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fewer than half of the studies included for this scoping review defined co‐design (or similar method used), and there was no unifying definition across any of the studies. McGill et al in their scoping review of 71 co‐produced interventions for the prevention of chronic disease highlighted the interchangeable use of co‐words such as ‘co‐design’, ‘co‐create’ and ‘co‐develop’ when describing the involvement of end users or intermediaries 69 . In this review we chose to include studies that demonstrated a partnership with consumers (as aligned with the final two levels on the IAP2 Public Participation Spectrum 15 ) to provide consistency in our definition.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al [ 11 ], have termed this the ‘cobiquity’ phenomenon where various co-words (e.g. co-production, co-design) are used interchangeably; this may breed confusion amongst researchers on what constitutes co-production and lead some to conflate meanings and associated practices [ 12 ]. A number of reviews have looked to address this confusion, exploring the use of co-production and/or co-design approaches in school-based health interventions [ 13 ], in health and social care [ 14 ], and in knowledge mobilisation of health conditions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient and public involvement and engagement (PPIE) in co‐producing health‐related research are growing rapidly on an international scale, with efforts across numerous countries recently described in a special issue of The BMJ 1 and other reviews. 2 , 3 , 4 , 5 In the United States, the Patient‐Centered Outcomes Research Institute (PCORI) 6 was created in 2012 to build the nation's capacity, production and dissemination of stakeholder‐driven research. (‘Stakeholder‐driven research’ is a phrase commonly used by PCORI and is conceptually similar to phrases such as PPIE as applied to research, co‐production of research, community‐based participatory research or participatory action research.)…”
Section: Introductionmentioning
confidence: 99%
“…Patient and public involvement and engagement (PPIE) in coproducing health-related research are growing rapidly on an international scale, with efforts across numerous countries recently described in a special issue of The BMJ 1 and other reviews. [2][3][4][5] In the United States, the Patient-Centered Outcomes Research Institute (PCORI) 6 was created in 2012 to build the nation's capacity, production and dissemination of stakeholder-driven research.…”
Section: Introductionmentioning
confidence: 99%